Vaccine-associated axillary lymphadenopathy with a focus on COVID-19 vaccines Impfassoziierte axillare Lymphadenopathie mit Fokus auf COVID-19-Impfstoffe - Wilpert, Caroline; Wenkel, Evelyn; Baltzer, Pascal Andreas Thomas; Fallenberg, Eva Maria; Preibsch, Heike; Sauer, Stephanie Tina; Siegmann-Luz, Katja; Weigel, Stefanie; Wunderlich, Petra; Wessling, Daniel (Röfo: Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2024)
Objective Axillary lymphadenopathy (LA) after COVID-19 vaccination is now known to be a common side effect. In these cases, malignancy cannot always be excluded on the basis of morphological imaging criteria. Method Narrative review for decision-making regarding control and follow-up intervals for axillary LA according to currently published research. This article provides a practical overview of the management of vaccine-associated LA using image examples and a flowchart and provides recommendations for follow-up intervals. A particular focus is on patients presenting for diagnostic breast imaging. The diagnostic criteria for pathological lymph nodes (LN) are explained. Results Axillary LA is a common adverse effect after COVID-19 vaccination (0.3-53%). The average duration of LA is more than 100 days. LA is also known to occur after other vaccinations, such as the seasonal influenza vaccine. Systematic studies on this topic are missing. Other causes of LA after vaccination (infections, autoimmune diseases, malignancies) should be considered for the differential diagnosis. If the LA persists for more than 3 months after COVID-19 vaccination, a primarily sonographic follow-up examination is recommended after another 3 months. A minimally invasive biopsy of the LA is recommended if a clinically suspicious LN persists or progresses. In the case of histologically confirmed breast cancer, a core biopsy without a follow-up interval is recommended regardless of the vaccination, as treatment appropriate to the stage should not be influenced by follow-up intervals. For follow-up after breast cancer, the procedure depends on the duration of the LA and the woman's individual risk of recurrence. Conclusion Vaccination history should be well documented and taken into account when evaluating suspicious LN. Biopsy of abnormal, persistent, or progressive LNs is recommended. Preoperative staging of breast cancer should not be delayed by follow-up. The risk of false-positive findings is accepted, and the suspicious LNs are histologically examined in a minimally invasive procedure. Key Points The vaccination history must be documented (vaccine, date, place of application). If axillary LA persists for more than 3 months after vaccination, a sonographic follow-up examination is recommended after 3 months. Enlarged LNs that are persistent, progressive in size, or are suspicious on control sonography should be biopsied. Suspicious LNs should be clarified before starting oncological therapy, irrespective of the vaccination status, according to the guidelines and without delaying therapy. Citation Format Wilpert C, Wenkel E, Baltzer PA et al. Vaccine-associated axillary lymphadenopathy with a focus on COVID-19 vaccines. Fortschr Röntgenstr 2024; DOI 10.1055/a-2328-7536.
CRIS-Team Scopus Importer:2024-07-19
Keywords: breast; breast radiography; covid-19 vaccine; lymphatic